2021
DOI: 10.3390/antiox10071020
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Melatonin on NLRP3 Inflammasome Activation in Diseases

Abstract: NLRP3 inflammasome is a part of the innate immune system and responsible for the rapid identification and eradication of pathogenic microbes, metabolic stress products, reactive oxygen species, and other exogenous agents. NLRP3 inflammasome is overactivated in several neurodegenerative, cardiac, pulmonary, and metabolic diseases. Therefore, suppression of inflammasome activation is of utmost clinical importance. Melatonin is a ubiquitous hormone mainly produced in the pineal gland with circadian rhythm regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 175 publications
2
25
0
Order By: Relevance
“…Heightened expression of the NLRP3 inflammasome was detected in leukocytes in the lungs of all patients who did not survive COVID-19 [ 491 ]. Melatonin targets NLRP3 inflammasome-mediated cytokine release employing antioxidant-dependent and -independent mechanisms [ 492 ].…”
Section: Melatonin Protects Mitochondria and Atp Production To Inhibi...mentioning
confidence: 99%
“…Heightened expression of the NLRP3 inflammasome was detected in leukocytes in the lungs of all patients who did not survive COVID-19 [ 491 ]. Melatonin targets NLRP3 inflammasome-mediated cytokine release employing antioxidant-dependent and -independent mechanisms [ 492 ].…”
Section: Melatonin Protects Mitochondria and Atp Production To Inhibi...mentioning
confidence: 99%
“…It has been found that many natural and endogenous or exogenous molecules exert anti-inflammatory effects by inhibiting NLRP3 inflammasome activation in OP. Arioz ect (70). have summarized the effect of melatonin, a widely used natural and endogenous molecule, on NLRP3 in a variety of different diseases.…”
Section: Potential Therapeutic Target Of Nlrp3 Inflammasome In Opmentioning
confidence: 99%
“…The NLRP3 inflammasome is a cytosolic multiprotein comprised of the NOD-like receptor, and adaptor and effector proteins that trigger the release of specific cytokines (e.g., IL-1β and IL-18) and initiate the innate immune system cascade, having an established role in the pathogenesis of numerous inflammatory conditions. As such, the inhibition of the NLRP3 inflammasome by melatonin as a result of its anti-inflammatory properties, could advance treatment options for a range of inflammatory conditions [15,16].…”
mentioning
confidence: 99%
“…In such a context, Arioz et al summarised the in vitro and in vivo studies that assessed this effect of melatonin on NLRP3 inflammasome-associated conditions [15]. It was concluded that melatonin can inhibit NLRP3 by regulating non-coding RNAs and has an overall anti-inflammatory effect with the inhibition of inflammatory pathways, such as NFκB, and the activation of mitophagy and the Nrf2/NFE2L2 pathway, diminishing ROS generation.…”
mentioning
confidence: 99%